Fumarato and phthalato bridged dinuclear metal–organic Cu(ii) and Mn(ii) compounds involving infinite fumarate–water assemblies and unusual structure-guiding H-bonded synthons: antiproliferative evaluation and theoretical studies. (6th September 2022) - Baishya, Trishnajyoti; Sharma, Pranay; Gomila, Rosa M.; Frontera, Antonio; Barcelo-Oliver, Miquel; Verma, Akalesh K.; Bhattacharyya, Manjit K.
Abstract : In vitro anticancer activities have been explored in fumarato and phthalato bridged dinuclear Cu(ii ) and Mn(ii ) compounds involving infinite fumarate–water assemblies and unusual structure-guiding H-bonded synthons. Abstract : Two new dinuclear coordination compounds viz. [Cu2 (μ-fum)(phen)2 (H2 O)6 ](fum)·6H2 O (1 ) and [Mn2 (μ-phth)2 (phen)4 ]·2H2 O (2 ) (phen = 1, 10-phenanthroline, fum = fumarate and phth = phthalate) have been synthesized and characterized by elemental analysis, single crystal X-ray diffraction studies, electronic, vibrational, and 1 H-NMR spectroscopy and thermogravimetric analysis. Compound 1 crystallizes as a co-crystal hydrate of Cu(ii ), whereas compound 2 is a dinuclear compound of Mn(ii ). Crystal structure analysis of compound 1 unfolds the presence of unconventional infinite fum–water assemblies involving the lattice fum and water molecules. To the best of our knowledge, this is the 1st report of an infinite anion–water cluster involving fum anions. The unusual dual enclathration of lattice water molecules in compound 2 and cooperative (π–π)2 /(π–π)1 /(π–π)2 ternary assemblies observed in compound 1 also provides additional reinforcement to the crystal structures. DFT calculations in combination with the NCI plot and QTAIM analyses have been carried out to explore the energetic features of the unusual structure directing H-bonded synthons involving the coordinated and non-coordinated water molecules with fum/phth ligands. The large interaction energies indicate the significance of these structures guiding H-bonded synthons for the stabilities of the compounds. The in vitro anticancer activities of the compounds considering cell cytotoxicity and apoptosis assays reveal that compound 1 showed significant concentration-dependent cytotoxicity in Dalton's lymphoma (DL) cancer cells with negligible effects on normal PBMCs. Molecular docking and pharmacophore modelling studies of the structure of compound 1 reveal that the compound considerably interacts with the active sites of antiapoptotic proteins to establish structure–activity relationships (SARs).